Opportunities and Challenges for Using Automatic Human Affect Analysis in Consumer Research - Küster, Dennis; Krumhuber, Eva G.; Steinert, Lars; Ahuja, Anuj; Baker, Marc; Schultz, Tanja (Frontiers in Neuroscience, 2020)
The ability to automatically assess emotional responses via contact-free video recording taps into a rapidly growing market aimed at predicting consumer choices. If consumer attention and engagement are measurable in a reliable and accessible manner, relevant marketing decisions could be informed by objective data. Although significant advances have been made in automatic affect recognition, several practical and theoretical issues remain largely unresolved. These concern the lack of cross-system validation, a historical emphasis of posed over spontaneous expressions, as well as more fundamental issues regarding the weak association between subjective experience and facial expressions. To address these limitations, the present paper argues that extant commercial and free facial expression classifiers should be rigorously validated in cross-system research. Furthermore, academics and practitioners must better leverage fine-grained emotional response dynamics, with stronger emphasis on understanding naturally occurring spontaneous expressions. We posit that applied consumer research might be better situated to examine facial behavior in socio-emotional contexts rather than decontextualized, laboratory studies, and highlight how AHAA can be successfully employed in this context. Also, facial activity should be considered less as a single outcome variable, and more as promising input for two-step machine learning in combination with other (multimodal) features. We illustrate this point in a case study using facial activity as input features to predict crying behavior in response to sad movies. Implications of this approach and potential obstacles that need to be overcome are discussed within the context of consumer research.